The stone artefacts from the Vredenburg Peninsular archaeological survey, west coast of South Africa - Sadr, K.; Gribble, J. (Southern African Humanities, 2010)
The stone artefacts and radiocarbon dates analysed from the Vredenburg Peninsular archaeological survey of 1991-92 show a 6000-year-long lithic sequence with an earlier, more formal set of assemblages and a later, more informal set. Between the two, a number of adze-rich sites seem to define a middle, or transitional phase in the local lithic sequence. This sequence suggests that the tripartite division of the pre-colonial Holocene industries on the west coast that was proposed by Jalmar Rudner in the 1960s represents a local evolution in lithic traditions.